2012
DOI: 10.5114/kitp.2012.32684
|View full text |Cite
|
Sign up to set email alerts
|

ANESTEZJOLOGIA I INTENSYWNA TERAPIA Inhaled nitric oxide effects outside the lungs – experimental and clinical evidence

Abstract: New evidence indicates that nitric oxide inhalation leads to formation of new compounds which may be carried as thiol groups attached to protein in blood or act indirectly through nitrite and nitrate, metabolites which have been shown to elevate over time during exposure to inhaled NO. Additionally it has been shown that inhaled nitric oxide has no hemodynamic effects on normally perfused tissue, but increases blood flow selectively in ischemic tissue. It has a simple route of administration, safety profile an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Because of these properties, iNO may serve as a rescue therapy for ischemic conditions in which collateral blood flow is important or until interventional or spontaneous reperfusion occurs. 13 In conclusion, this study found that a therapeutic option of a combination of inhaled NO and IV steroids induced significant multifactorial effects with improvements in hemodynamics and oxygen transport while also diminishing the systemic inflammatory response in an experimental model of SRACC-induced I/R injury.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Because of these properties, iNO may serve as a rescue therapy for ischemic conditions in which collateral blood flow is important or until interventional or spontaneous reperfusion occurs. 13 In conclusion, this study found that a therapeutic option of a combination of inhaled NO and IV steroids induced significant multifactorial effects with improvements in hemodynamics and oxygen transport while also diminishing the systemic inflammatory response in an experimental model of SRACC-induced I/R injury.…”
Section: Discussionmentioning
confidence: 60%
“…Because of these properties, iNO may serve as a rescue therapy for ischemic conditions in which collateral blood flow is important or until interventional or spontaneous reperfusion occurs. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation